The efficiency model of goalkeeper's actions in soccer - Szwarc, A.; Lipinska, P.; Chamera, M. (Baltic Journal of Health and Physical Activity, 2010)
Background: The purpose of this paper was to present cognitive models illustrating efficiency of the goalkeeper's actions in soccer based on observation of play in selected matches of the Euro 2008 finals.